Sustainability Performance and Its Impact on Financial Distress Risk—Evidence From STOXX Europe 600 - Marcel Seefloth; Florian Siedler; Christoph Kayser; Benedikt~T. Retsch; Henning Zülch (Business Strategy and the Environment, 2025)
Sustainability performance (SP) has emerged as a central topic on both corporate and political agendas worldwide. This study investigated the relationship between SP and financial distress risk (FDR) among European listed firms, addressing the growing importance of SP in financial decision-making. Utilising a panel dataset from LSEG Data & Analytics (formerly Refinitiv) for STOXX Europe 600 firms between 2016 and 2022, we performed regression analyses to examine the impact of SP on FDR, measured through alternating scores. In contrast to most existing research, we found SP to increase FDR for most analyses performed, with the effect varying by SP dimension. Because we found environmental and governance SP to increase FDR, we did not find an association between social SP and FDR in most analyses performed. Our findings provide practical and theoretical implications for firms, investors and policymakers concerning the influence of SP investments on FDR and potential SP overinvestments in Europe's latest sustainability regulatory setting.
Keywords: 330; Altman Z-score; ESG; Europe; financial distress risk; STOXX Europe 600; sustainability performance